Unveiling inflation: Oil shocks, supply chain pressures, and expectations - Knut Are Aastveit; Hilde Christiane Bjørnland; Jamie Cross; Helene Olsen (Norges Bank, 2024)
This paper demonstrates that inflation expectations have acted as significant amplifiers of recent global demand and supply shocks, thereby playing a crucial role in maintaining inflation at relatively high levels. This finding is established by applying a structural vector autoregression model that includes various shocks to global demand and supply, along with domestic inflation and inflation expectations for six economies: the United States, Canada, New Zealand, the Euro area, the United Kingdom, and Norway. We begin by documenting that global demand and supply shocks in the oil market, as well as global supply chain disruptions, have been major drivers of the recent inflation surge in all these economies. Subsequently, through various counterfactual and conditional forecasting exercises, we demonstrate that inflation expectations generally amplify the transmission of global shocks to inflation and have played a critical role in sustaining elevated inflation rates in recent years, particularly in the United States, Canada, and New Zealand.
hdl:11250/3176403
Keywords: E31; C11; C32; D84; Q41; Q43; 330; Inflation Expectations; Inflation Pass-through; Oil Prices; Supply Chain Pressures